Layanan Bimbingan Konseling terhadap Anak Berkebutuhan Khusus kelas IV Sekolah Dasar Mahira - Azizah Munawaroh; Sherly Arlena Utami; Piki Apsir Pratama; Zubaidah (Yayasan Darussalam Bengkulu, 2023)
This study aims to find out how the BK service is for Children with Special Needs at Mahira Sekolah Alam Benkulu, where this study uses interview methods and direct observation on the spot, namely at Mahira. Guidance and counseling services are very important services for students, especially for Children with Special Needs (ABK). The results of the study show that BK services at Mahira do not yet exist, because at the elementary school level there are no special guidance and counseling services, but at Mahira BK services are provided to students, especially for Children with Special Needs through homeroom teachers and accompanying teachers, in one class there are 3-5 teachers, namely homeroom teachers and accompanying teachers. Through accompanying teachers, students can be directed and can solve their problems.